Strategi Komunikasi Dalam Sosialisasi Pemilu Untuk Memotivasi Masyarakat Dalam Menggunakan Hak pilih melalui Instagram - Widiantari, Komang Sri; Maharani, Dian Putri (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Public participation in elections is important to strengthen democracy. Communication strategies through Instagram are important to raise awareness of this. With public education and strong campaigns, this strategy can build a better understanding of the importance of elections. Instagram acts as a strategic tool in stimulating public participation. This research shows the importance of effective communication strategies in encouraging participation through Instagram in the context of elections. It shows that video content and posts can shift people's paradigms and trigger their interest in participating as agents of change in building democracy.